1996
DOI: 10.1111/j.1365-2133.1996.tb03847.x
|View full text |Cite
|
Sign up to set email alerts
|

Nodular localized cutaneous amyloidosis: detection of monoclonality of infiltrating plasma cells by polymerase chain reaction

Abstract: We report nodular localized cutaneous amyloidosis arising in a 74-year-old woman as a single nodule at the left angle of the mouth. Histological examination revealed eosinophilic material deposited in the dermis, identified as amyloid by staining with Dylon stain, and antiamyloid P component, and by electron microscopy. The amyloid material was further determined immunohistochemically to be of AL fibril protein type derived from lambda light chains. Infiltrating plasma cells, around blood vessels in the dermis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Some studies have demonstrated monoclonality of this infiltrate in most cases but not in all. [213][214][215] In these patients, however, a systemic involvement must strictly be excluded due to its bad prognosis. 215 In this respect, gene rearrangement studies could be useful in the early detection of systemic AL amyloidosis which presents as cutaneous involvement as its first manifestation.…”
Section: Nodular Amyloidosismentioning
confidence: 99%
“…Some studies have demonstrated monoclonality of this infiltrate in most cases but not in all. [213][214][215] In these patients, however, a systemic involvement must strictly be excluded due to its bad prognosis. 215 In this respect, gene rearrangement studies could be useful in the early detection of systemic AL amyloidosis which presents as cutaneous involvement as its first manifestation.…”
Section: Nodular Amyloidosismentioning
confidence: 99%
“…7 8 Furthermore, we suggested that clonal expansion of plasma cells in nodular localised cutaneous amyloidosis occurs locally, because plasma cells in a skin lesion showed monotypic staining with anti-antibody, while the adjacent normal skin contained plasma cells stained with both anti-and antiantibodies. 7 Laeng et al have reported similar results for nervous system amyloidomas. 17 In the present study, we obtained the results by two diVerent methods-immunohistochemistry and PCR: plasma cells with monotypic staining for immunoglobulin light chains were observed adjacent to amyloid deposits, while those showing either staining were located peripherally; and there was a distinct band on a polyclonal smear.…”
Section: Discussionmentioning
confidence: 64%
“…Semi-nested PCR amplification for the rearranged VDJ region of the immunoglobulin heavy chain gene was performed as previously described with slight modifications. 3,[8][9][10][11] Briefly, DNA was extracted from paraffin-embedded sections and used as a template in the first round of PCR amplification (30 cycles) with consensus primers, forward primer FR3A and outer reverse primer LJH. [8][9][10] Using the resulting PCR products, the second round of PCR (30 cycles) with FR3A and inner reverse primer VLJH was performed.…”
Section: Methodsmentioning
confidence: 99%
“…2 We recently described a case of NLCA and demonstrated monoclonality of infiltrating plasma cells by semi-nested polymerase chain reaction (PCR). 3 In this study we analyse further paraffin-embedded sections.…”
mentioning
confidence: 99%